Do Short-Term Improvements in Activities of Daily Living and Instrumental Activities of Daily Living Have Association With Return to Work in Workers With Occupational Injury? From an Occupational Injury Cohort in Taiwan - Fa-Chen Lin; Chia-Pin Lin; Hung-Yi Chuang; Tse-Wei Wu; Peng-Ju Huang; Chen-Cheng Yang; Chao-Hung Kuo (Safety and Health at Work, 2025)
Background: Rates of return to work (RTW) after an occupational injury vary considerably according to a range of factors. Limited studies have been conducted on the specific correlation between RTW and functional assessments, including activities of daily living (ADL) and instrumental activities of daily living (IADL). This prospective cohort study aims to determine if a relationship exists between ADL/IADL and RTW among injured workers in Taiwan. Methods: We recruited 162 workers who reported work-related injuries from January 2023 to May 2024. The assessment of ADL was evaluated using the Barthel Index, whereas IADL was evaluated using the Lawton Instrumental Activities of Daily Living scale. ADL/IADL were assessed immediately after the injury, at 3 and 6 months postinjury. Logistic regression models were used for the connections between ADL, IADL, and RTW while considering various confounding factors. Results: The mean ADL and IADL improved significantly at both 3 and 6 months postinjury. Logistic regression analysis indicated that IADL scores at 3 and 6 months postinjury were significantly linked to RTW. ADL scores lost significance after adjustment. Age was negatively associated with RTW, whereas sex and labor insurance status showed no significant association. Conclusion: Short-term improvements in IADL are linked to successful RTW, rather than ADL for occupationally injured workers. Evaluations of IADL should be incorporated into rehabilitation plans to predict and improve RTW. Thorough rehabilitation approaches that address various aspects of functional abilities may be crucial to support successful RTW. Further studies are required to validate these results.